Cross-cultural adaptation and validation of the CFAbd-Score for gastrointestinal symptoms in patients with cystic fibrosis - Flávia N.S. Infante; Elizete A. Lomazi; Carlos Zagoya; Franziska Duckstein; Daniela O. Magro; Fernando Pessotto; Antônio F. Ribeiro; José D. Ribeiro; Jochen G. Mainz (Jornal de Pediatria)
Objective: Translating and cross-culturally adapting the CFAbd-Score, Cystic Fibrosis (CF) Abdominal Score, to use in Brazilian spoken Portuguese. The CFAbd-Score is a questionnaire for assessing CF-related abdominal symptoms and their influence on the quality of life (QoL). It comprises 28 questions on five domains: abdominal pain, bowel movements, eating and appetite, gastroesophageal reflux symptoms, and the impact of gastrointestinal (GI) symptoms on QoL. Method: Cross-cultural adaptation included assessment of conceptual and item equivalence, semantic, operational, and measurement equivalence. Content validity was assessed. The validation and psychometric analysis phase included 97 people with CF (pwCF), median age:14.58y (IQR 9/19), and 105 healthy individuals, 15.10y (IQR 9/20). Exploratory factor analysis (FA) identified retained factors. Internal consistency of the extracted domains was evaluated using Cronbach's α, and the Kaiser-Meyer-Olkin test (KMO) was used to check the sample adequacy. Bartlett's test tested the null hypothesis that the correlation matrix is an identity matrix. Results: All items were considered relevant to the construct and good semantic equivalence of the version was recognized. FA showed the appropriate weight of all items and good internal consistency, with Cronbach's alpha 0.89. Bartlett's test significance level (p < 0.001) and KMO coefficient of 0.72 indicated good adequacy for structure. Internal consistency coefficients (Cronbach's alpha) were good for abdominal pain: 0.84; abdominal bloating: 0.73; flatulence: 0.76; heartburn: 0.81, and low for reflux: 0.54. Conclusion: The CFAbd-Score was adapted to the Brazilian spoken Portuguese and demonstrated content and semantic equivalence. The final version showed appropriate validity, and internal consistency, preserving the psychometric properties of the original version.